Severe early onset obesity and hypopituitarism in a child with a novel SIM1 gene mutation. (6th October 2020) - Gonsalves, Rob; Aleck, Kirk; Newbern, Dorothee; Shaibi, Gabriel; Kapadia, Chirag; Oatman, Oliver
Abstract : Summary : Single-minded homolog 1 (SIM1) is a transcription factor that plays a role in the development of both the hypothalamus and pituitary. SIM1 gene mutations are known to cause obesity in humans, and chromosomal deletions encompassing SIM1 and other genes necessary for pituitary development can cause a Prader–Willi-like syndrome with obesity and hypopituitarism. There have been no reported cases of hypopituitarism linked to a single SIM1 mutation. A 21-month-old male presented to endocrinology clinic with excessive weight gain and severe obesity. History was also notable for excessive drinking and urination. Endocrine workup revealed central hypothyroidism, partial diabetes insipidus, and central adrenal insufficiency. Genetic evaluation revealed a novel mutation in the SIM1 gene. No other genetic abnormalities to account for his obesity and hypopituitarism were identified. While we cannot definitively state this mutation is pathogenic, it is notable that SIM1 plays a role in the development of all three of the patient's affected hormone axes. He is now 6 years old and remains on treatment for his pituitary hormone deficiencies and continues to exhibit excessive weight gain despite lifestyle interventions. Learning points: Mutations in SIM1 are a well-recognized cause of monogenic human obesity, and there have been case reports of Prader–Willi-like syndrome and hypopituitarism in patients with chromosomal deletions that contain the SIM1 gene. SIM1 is expressed during the development of the hypothalamus, specifically in neuroendocrine lineages that give rise to the hormones oxytocin, arginine vasopressin, thyrotropin-releasing hormone, corticotropin-releasing hormone, and somatostatin. Pituitary testing should be considered in patients with severe obesity and a known genetic abnormality affecting the SIM1 gene, particularly in the pediatric population.